[Rezension von: J. C. Kinkley, Corruption and realism in late socialist China] - Senz, Anja-Désirée (Historische Literatur, 2008)
Rezension zu / Review of: Kinkley, Jeffrey C.: : Corruption and Realism in Late Socialist China. The Return of the Political Novel